On the Description of Individual Course Units for Programme Assessment and Better Syllabuses - Barros, João Paulo (2015)
Presently, higher education programmes are being assessed at several different levels, locally, or even countrywide. In this paper, we propose a template for the description of each curricular unit in higher education programmes that seeks to promote reflective teaching, widely acknowledged as fundamental to improve practices leading to improved student learning, while being advantageous and convenient for programme assessment by external entities. To this end, we take as a starting point the template that all Portuguese higher education institutions have to fill for each curricular unit, for programme assessment purposes. Based on the literature, we argue this new template format fosters teacher reflection and provides additional and easier to compare data for accreditation boards, and the whole education community, most notably, students. Finally, we argue that it can and should be used to improve syllabuses.